Building Kuwait’s Future, One Small Enterprise at a Time - Abukumail, Ali H.; Karam, Nadia; Al-Otaibi, Ghanimah (World Bank, Washington, DC, 2016)
The number of Small-to-Medium enterprises (SMEs) in Kuwait is high, particularly in retail and non-financial services, but their overall contribution to the economy is marginal—just 3% of GDP. This paradox is especially troubling when compared to high income and emerging economies, where SMEs comprise most of the economic activity in the private sector and contribute to 50% and 40% of GDP (respectively). According to a recent survey of nearly 50,000 firms in 104 countries, SMEs provide as much as two-thirds of all employment, with small firms contributing more to employment in low-income countries than high-income countries.